1994
DOI: 10.1007/bf02540462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alkali metal ions on gel formation in the 12‐hydroxystearic acid/soybean oil system

Abstract: It has been known that 12-hydroxystearic acid (12HSA) forms a thermoreversible gel with a fibrous associated network in organic solvents. Mechanically durable gels were induced by the addition of small amounts of alkali metal ions, which can be supplied in the form of alkali metal salts of 12HSA (abbreviated as 12HS-M), even at a lower concentration range of gelling agent than with 12HSA alone. The structure of the networks was investigated by infrared spectrometry (IR), circular dichroism (CD) and scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 21 publications
1
24
0
Order By: Relevance
“…Examples of single components that are capable of structuring edible oils are diglycerides, monoglycerides and fatty acids [1][2][3][4][5][6][7], wax esters, sorbitan monostearates, ceramides, waxes, fatty alcohols, dicarboxylic acids and derivatised fatty acids [8][9][10][11][12][13][14][15][16]. Examples of mixed systems are fatty acids ?…”
Section: Introductionmentioning
confidence: 99%
“…Examples of single components that are capable of structuring edible oils are diglycerides, monoglycerides and fatty acids [1][2][3][4][5][6][7], wax esters, sorbitan monostearates, ceramides, waxes, fatty alcohols, dicarboxylic acids and derivatised fatty acids [8][9][10][11][12][13][14][15][16]. Examples of mixed systems are fatty acids ?…”
Section: Introductionmentioning
confidence: 99%
“…In some substances, presence of impurities has a significant effect on properties of the product, e.g., some impurities affect growth rate of certain crystallographic faces, so that the morphology of the crystal changes. In the case of 12-HSA gel, it has been shown that hydrogen bonding between hydroxyl groups is important in formation of the crystalline fibers and "head to head" contacts are formed between carboxylic acid groups as observed in many fatty acids [9,10]. Existence of different component has a possibility to arrest formation of the hydrogen bonding and consequently growth of the crystalline fibers.…”
Section: Introductionmentioning
confidence: 99%
“…The structural characteristics of the low molecular-weight gelator are as follows: the presence of multiple functional groups capable of relatively weak physical molecular interactions such as van der Waals forces, hydrogen bonding, electrostatic forces, π-π stacking, and London dispersion forces; asymmetrical, non-planar, and bulky structures which relate to the suppression of crystal packing. Up to date, a large number of low molecular-weight organic substances, such as (R)-12-hydroxystearic acid (HSA) (Tachibana et al, 1979(Tachibana et al, , 1980Tamura et al, 1994;Rogers & Marangoni, 2009), 1,3;2,4-dibenzylidene-D-sorbitol (Wolfe et al, 1942), and amino acid derivatives (Hanabusa et al, 1999;Hanabusa, 2005;Suzuki et al, 2006) are known to form thermo-reversible gels with supramolecular nanofibrous network in organic solvents (Fig.2). Interest in these compounds originated in the petrochemical industry to immobilize flammable solvents and to aid in the clean up of oil spills (Abdallah & Weiss, 2000;Bhattacharya & Krishnan-Ghosh, 2001).…”
Section: Introductionmentioning
confidence: 99%